ADVERTISEMENT ANALYSIS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Ad analysis is a comprehensive evaluation of various elements to understand the impact and effectiveness of an advertisement. It helps businesses make informed decisions, refine their advertising strategies, and improve their overall marketing efforts.